Psychiatric emergency care during Coronavirus 2019 (COVID 19) pandemic lockdown: results from a Department of Mental Health and Addiction of northern Italy - Capuzzi, Enrico; Di Brita, Carmen; Caldiroli, Alice; Colmegna, Fabrizia; Nava, Roberto; Buoli, Massimiliano; Clerici, Massimo (Psychiatry research, 2020)
•The current COVID-19 pandemic is causing severe mental health problems.•We investigated the characteristics of emergency psychiatric consultations during the phase 1 of lockdown in a Department of Mental Health and Addiction located in Lombardy region, Italy, compared to similar period of 2019.•There was a marked reduction in the number of psychiatric emergency consultations.•Some patients were significantly more likely to present to emergency psychiatric consultations during lockdown.•COVID-19 epidemic may have a negative impact on more vulnerable individuals. The current COVID-19 pandemic and the consequent containment measures are leading to increasing mental health issues both in psychiatric patients and general population. We aimed to compare the number and characteristics of emergency psychiatric consultations during the phase 1 of lockdown with respect to the same period in 2019 in a Department of Mental Health and Addiction (DMHA) located in Lombardy region. We conducted a cross-sectional study including subjects consecutively admitted to two psychiatric emergency rooms of DMHA in Monza, Lombardy, Italy. Sociodemographic data, clinical characteristics, referred symptoms, diagnosis and information on patients’ illness course following the emergency consultations were collected. No subjects were excluded for the purposes of the study. Between February 21st and May 3rd 2020, there was a marked reduction in the number of psychiatric emergency consultations, if compared to the same period of 2019. Subjects who were living in psychiatric residential treatment facilities, had cannabis addiction and a diagnosis of obsessive-compulsive disorder were significantly more likely to present to emergency psychiatric consultations during lockdown. COVID-19 epidemic may have a negative impact on more vulnerable individuals. Strategies to enhance relapse prevention and the use of alternative approaches as e-health technologies should be promoted.